2009
DOI: 10.1029/2008gl036282
|View full text |Cite
|
Sign up to set email alerts
|

Coral reefs may start dissolving when atmospheric CO2 doubles

Abstract: [1] Calcification rates in stony corals are expected to decline significantly in the near future due to ocean acidification. In this study we provide a global estimate of the decline in calcification of coral reefs as a result of increase in sea surface temperature and partial pressure of CO 2 . This estimate, unlike previously reported estimates, is based on an empirical rate law developed from field observations for gross community calcification as a function of aragonite degree of saturation (W arag ), sea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
242
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 280 publications
(257 citation statements)
references
References 30 publications
11
242
0
1
Order By: Relevance
“…Therefore, we need to move beyond simple correlations in order to evaluate what is controlling the calcification rates measured in this study. Silverman et al (2009) and Anthony et al (2011) took the approach of defining functions that attempted to describe the combined effects of temperature and X arag on coral calcification. These functions did not include the effect of light, which certainly is important in explaining seasonal differences nor did they take into account that coral growth often has an asymmetric response to temperature (Houck et al 1975;Reynaud et al 1999).…”
Section: Environmental Controls On Seasonal Differences In Growth Ratesmentioning
confidence: 99%
“…Therefore, we need to move beyond simple correlations in order to evaluate what is controlling the calcification rates measured in this study. Silverman et al (2009) and Anthony et al (2011) took the approach of defining functions that attempted to describe the combined effects of temperature and X arag on coral calcification. These functions did not include the effect of light, which certainly is important in explaining seasonal differences nor did they take into account that coral growth often has an asymmetric response to temperature (Houck et al 1975;Reynaud et al 1999).…”
Section: Environmental Controls On Seasonal Differences In Growth Ratesmentioning
confidence: 99%
“…Most empirical studies of the effects of OA on coral reefs have reported a positive correlation between calcification rates and aragonite saturation state (V arag ) [5], supporting pessimistic projections forecasting the disappearance of most coral reefs before the end of the current century [6][7][8]. However, recent studies now indicate more nuanced responses to OA for select reef calcifiers [9], with a compilation of laboratory studies of corals suggesting that coral calcification will decline approximately 10-20% (rather than ceasing) for a doubling of present-day partial pressure of CO 2 (pCO 2 ) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Dramatic deterioration of reef health has occurred over the past few decades and is predicted to continue due to rapidly increasing sea surface temperatures (SSTs) and ocean acidification, resulting in increased bleaching frequency and severity, and reduced calcification and reef accretion (e.g. Hoegh-Guldberg et al 2007;Silverman et al 2009). High-latitude reefs are of particular concern as they are already considered to be a marginal reefal environment (Veron 1995;Kleypas et al 1999a;Guinotte et al 2003).…”
Section: Introductionmentioning
confidence: 99%